Development of modern immunization agent against bovine papillomavirus type 1 infection based on BPV1 L1 recombinant protein - Vrablikova, Alena; Brezani, Veronika; Psikal, Ivan; Fraiberk, Martin; Sebela, Marek; Fojtikova, Martina; Kulich, Pavel; Hezova, Renata; Masek, Josef (Frontiers in Veterinary Science, 2023)
Bovine papillomavirus type 1 L1 protein was produced in a baculovirus expression system and purified as virus-like particles (VLPs) by affinity chromatography using lectins. The morphological integrity of VLPs was confirmed by electron microscopy. Differences between the two detected variants were deciphered by mass spectrometry of peptides (MALDI-TOF). Mice were immunized with purified VLPs in doses of 10, 25, or 50 μg in combination with 1% saponin and 15% alhydrogel per dose as adjuvants. Analysis of the humoral immune response revealed increased levels of specific antibodies detected 3 weeks after the first immunization in all groups of animals. This was further significantly increased by the booster applied 3 weeks after the first dose, with the best immune response in a group of mice immunized by the largest dose of antigen. BPV1 L1 VLPs purified by affinity chromatography using lectins could be used for prophylactic immunization in veterinary medicine.